Influence of Smartphone Usage on development of Sexuality among Late Adolescent Boys in Health Sciences Colleges of South India [version 2; peer review: 2 approved] - Sara J Ommen; Preeti M Galagali; Sharath M Manya; Prasanna Mithra; Jayashree K (F1000Research)
Background Better affordability of data plans and an increase in “budget” smartphones have resulted in an exponential rise in internet and smartphone users. The ease of access to sexually explicit material (SEM) coupled with adolescents’ impulsivity makes them prone to excessive SEM exposure and may affect the development of sexuality via the perceived realism of such content. This study was done to study the influence between problematic smartphone usage (PSU) and sexuality development among late adolescent boys. Methods One hundred and thirty-four adolescents aged 18-19 years, studying in a medical university, participated in this cross-sectional study. Smartphone Addiction Scale – short version (SAS-SV) to evaluate PSU and a content validated semi-structured proforma to evaluate gender identity, sexual orientation, sources of information on pubertal changes, and exposure to pornographic content was used. We expressed results as proportion and summary measures (Mean±SD), Chi-square test to find influence between PSU and adolescent sexuality development. Results We found a 45.5% prevalence of PSU. Among study participants, 88% were attracted to the opposite sex, 6% were attracted to the same-sex, and 6% were attracted to both sexes. Three per cent of participants liked wearing clothes of the opposite sex, 7.5% wanted to be members of the opposite sex, whereas 10.4% were not comfortable with their genitalia. They obtained information regarding pubertal changes from friends (85) and media (78). Many had exposure to pornographic content (90%), with the youngest being nine years old. Conclusion Nearly half of the late adolescents have PSU. Pornographic contents are accessed through Smartphones.